A Study on Consumer Attitude and Behavior towards Purchasing of Green Products - Preetha, G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The evolving climate conditions have proven to be hazards created by the man-made activities. The global warming is causing panic among the environmentalists to safeguard the environment. The consumerism of the modern world has created significant environmental impact on the Earth. The remains of the consumerism are having vital effect on the other living organisms. The role of the disposal has become mandatory for safeguarding the environment. The change in the consumer attitude and behavior has to be modified for the welfare of the future generation. The awareness and activities of the consumers have to enhance at quicker pace to safeguard the environment from further damage. This paper engages to study the awareness level of the consumers towards the green product and to study the green buying behavior of the consumers. The study has been conducted at micro level with 120 samples who are being the consumers of green products. The study has adopted simple random sampling for the selection of the sample from the green product users. The various statistical tools used in the study are percentage analysis, chi-square test and analysis of variance. The results of the study reveal that the consumers are having significant awareness about the green products and most effective methods that influences the green products purchases are attractive as well as informative advertisements. The green product holds the future of environment and examines the consuming habits of the existing consumers. The role of green products is crucial in protecting the environment and making the environment sustainable.